2000
DOI: 10.1128/aem.66.10.4180-4186.2000
|View full text |Cite
|
Sign up to set email alerts
|

Differential C Isotope Discrimination by Fungi during Decomposition of C3- and C4-Derived Sucrose

Abstract: Stable isotope analysis is a major tool used in ecosystem studies to establish pathways and rates of C exchange between various ecosystem components. Little is known about isotopic effects of many such components, especially microbes. Here we report on the discovery of an unexpected pattern of C isotopic discrimination by basidiomycete fungi with far-reaching consequences for our understanding of isotopic processing in ecosystems where these microbes mediate material transfers across trophic levels. We measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 42 publications
(82 reference statements)
8
94
2
Order By: Relevance
“…The fractionation during rhizomicrobial respiration may occur during two processes: (1) root-derived carbon compounds in the rhizosphere (or rhizodeposition) may have different δ 13 C values than root biomass (Werth and Kuzyakov 2005); and (2) microbially respired CO 2 may be different in δ 13 C value with the root-derived carbon substrates taken up and utilized by them Henn and Chapela 2000;Mary et al 1992). The first process is mainly determined by the chemical composition of rhizodeposition, which is a mixture of different compounds (Lynch and Whipps 1990) that may differ significantly in δ 13 C value (Bowling et al 2008).…”
Section: Possible Mechanisms For 13 C Fractionation During Rhizosphermentioning
confidence: 99%
See 1 more Smart Citation
“…The fractionation during rhizomicrobial respiration may occur during two processes: (1) root-derived carbon compounds in the rhizosphere (or rhizodeposition) may have different δ 13 C values than root biomass (Werth and Kuzyakov 2005); and (2) microbially respired CO 2 may be different in δ 13 C value with the root-derived carbon substrates taken up and utilized by them Henn and Chapela 2000;Mary et al 1992). The first process is mainly determined by the chemical composition of rhizodeposition, which is a mixture of different compounds (Lynch and Whipps 1990) that may differ significantly in δ 13 C value (Bowling et al 2008).…”
Section: Possible Mechanisms For 13 C Fractionation During Rhizosphermentioning
confidence: 99%
“…It remains unclear whether 13 C fractionation during rhizosphere respiration also differs among species, particularly between C 3 and C 4 plants. Some previous studies have reported differences in 13 C fractionation during root respiration between a C 3 plant and a C 4 plant (Schnyder and Lattanzi 2005), fungal respiration of sucrose derived from C 3 and C 4 plants (Henn and Chapela 2000), and microbial decompositions of residues of C 3 and C 4 plants Schweizer et al 1999). Undoubtedly, the issue of 13 C isotopic fractionation associated with rhizosphere respiration requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The isotope effects of decomposition, for example, have had comparably less attention and are less 144 well understood as a result (Henn and Chapela, 2000). Even within the same fruiting body there can 145 be appreciable differences (± 2 ‰) in 15 values, suggesting they reflect local habitat substrate conditions (see SI).…”
Section: Et Al (2012) Demonstrated Mycorrhizal 139mentioning
confidence: 99%
“…In any case, it is necessary to look below ground to see what is really happening (Lilleskov & Bruns, 2001). Analyses of 13 C and 15 N isotopic signatures have a significant potential to provide information in this area (Hobbie et al ,, although further investigation is required to understand the isotopic enrichment phenomenon (Henn & Chapela, 2000). Combined community/population structure and function studies applying genomics may, in the future, significantly promote our understanding of the interactions between mycorrhizal fungal species with their hosts and with their biotic and abiotic environment.…”
Section: Bridging Genomics and Molecular Ecologymentioning
confidence: 99%